2000
DOI: 10.1126/science.287.5450.131
|View full text |Cite
|
Sign up to set email alerts
|

DNA Topoisomerase IIβ and Neural Development

Abstract: DNA topoisomerase IIbeta is shown to have an unsuspected and critical role in neural development. Neurogenesis was normal in IIbeta mutant mice, but motor axons failed to contact skeletal muscles, and sensory axons failed to enter the spinal cord. Despite an absence of innervation, clusters of acetylcholine receptors were concentrated in the central region of skeletal muscles, thereby revealing patterning mechanisms that are autonomous to skeletal muscle. The defects in motor axon growth in IIbeta mutant mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
258
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(273 citation statements)
references
References 26 publications
14
258
0
1
Order By: Relevance
“…Recent studies have demonstrated that muscle is pre-specialized in the central, prospective synaptic region prior to and independent of innervation, and these findings have led to a revised view of the steps and mechanisms that regulate neuromuscular synapse formation (Flanagan-Steet et al, 2005;Lin et al, 2001;Panzer et al, 2006;Yang et al, 2001;Yang et al, 2000). Key features of postsynaptic differentiation are established in a muscleautonomous, MuSK-dependent manner and motor neurons refine and sharpen, rather than induce this prepattern of postsynaptic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated that muscle is pre-specialized in the central, prospective synaptic region prior to and independent of innervation, and these findings have led to a revised view of the steps and mechanisms that regulate neuromuscular synapse formation (Flanagan-Steet et al, 2005;Lin et al, 2001;Panzer et al, 2006;Yang et al, 2001;Yang et al, 2000). Key features of postsynaptic differentiation are established in a muscleautonomous, MuSK-dependent manner and motor neurons refine and sharpen, rather than induce this prepattern of postsynaptic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…AChR gene expression and AChR clusters are concentrated in the central region of skeletal muscle in the absence of innervation (Lin et al, 2001;Yang et al, 2001;Yang et al, 2000). This nerve-independent patterning of AChR expression, termed muscle prepatterning, is dependent upon MuSK (Lin et al, 2001;Yang et al, 2001), a receptor tyrosine kinase that is activated by Agrin and essential for neuromuscular synapse formation (DeChiara et al, 1996;Strochlic et al, 2005).…”
Section: Musk Expression Is Patterned In Muscle Lacking Motor Axonsmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of topo IIα expression have been seen in aggressive proliferating tumours, whereas topo IIβ appears to be expressed ubiquitously in quiescent cells (Turley et al, 1997). Topo IIα is essential for survival of eucaryotic cells (Wang, 1996), while topo IIβ does not appear to be essential for either proliferation or survival (Yang et al, 2000;Herzog et al, 1998). Such findings may help explain the greater clinical utility of etoposide versus amsacrine.…”
Section: Resultsmentioning
confidence: 99%